Peptide‐Conjugated Silver Nanoparticles for the Colorimetric Detection of the Oncoprotein Mdm2 in Human Serum. Issue 4 (9th March 2022) - Retout, Maurice; Gosselin, Bryan; Mattiuzzi, Alice; Ternad, Indiana; Jabin, Ivan; Bruylants, Gilles
Abstract: Invited for this month's cover are the collaborating groups of Prof. Gilles Bruylants and Prof. Ivan Jabin, Université libre de Bruxelles, Belgium. The cover picture shows the principle of a colorimetric sensor, based on peptide‐conjugated silver nanoparticles, for the detection of the cancer biomarker Mdm2. The particles were functionalized via a recently developed strategy based on the use of calixarene diazonium salts. The calixarene‐based coating provides an unprecedented stability to the silver nanoparticles, enabling their use as colorimetric reporters for in vitro diagnostics. The cover was designed by I. Jabin. More information can be found in the Research Article by I. Jabin, G. Bruylants, and co‐workers . Abstract : "Silver nanoparticles (AgNPs) coated with PEGylated calixarenes and conjugated to peptide aptamers were used for the colorimetric detection of Mdm2 in human serum via a dual‐trapping strategy." (DOI: 10.1002/cplu.202100450 ).